The Polemics of the Old and the Young Minangkabau Youth About the Prophet's Household in the Book of Al Bashair (Text Editing and Content Analysis) - Amin, Saiful; Hendri, Hendri (Universitas Islam Negeri Sumatera Utara, 2025)
The polemics of the debate between the old and the young in the 19th century in Minangkabau no longer dwell on issues of worship and Sufism, taken for granted . But it has shifted to the realm of muamalah or precisely fiqh munakahat, namely: about the household of the Prophet Muhammad, this is found in the book of al bashair by abdul karim amrullah. this article aims to describe more deeply about the book of al bashair in the editing of the text of the content analysis fund and how the polemics about the household of the apostleullah in the book of al bashair. The research method uses qualitative methods with the type of library research with data collection methods of document study, inventory, codicology and interviews and the primary data source is the manuscript of kitab al bashair and descriptive data analysis techniques The results in this study are in general there are 3, namely the lack of religious knowledge of the local community, differences in religious understanding in Minangkabau and the condition of the local community at that time (between the old and the young in Minangkabau) in the book of pelita. polemics in kitab al bashair are caused by the influence of political factors, and sociocultural between you old and young.